Respuesta :

we are given

[tex] \frac{(x^2+x-6)}{(x^2-4)}*\frac{(x^2-9)}{(x^2+6x+9)} [/tex]

step-1: Factor terms

[tex] x^2+x-6=(x+3)(x-2) [/tex]

[tex] x^2+6x+9=(x+3)^2 [/tex]

[tex] x^2-4=(x-2)(x+2) [/tex]

now, we can plug these values

and we get

=[tex] \frac{(x+3)(x-2)}{(x-2)(x+2)}*\frac{(x-3)(x+3)}{(x+3)^2} [/tex]

step-2: Cancel common terms

we get

=[tex] \frac{(x+3)}{(x+2)}*\frac{(x-3)}{(x+3)} [/tex]

we can again cancel numerator and denominator

and we get

=[tex] \frac{(x-3)}{(x+2)} [/tex].............Answer


ACCESS MORE